D Radiotranscriptomic analysis of perivascular adipose tissue quantifies vascular inflammation in covid-19 from routine CT angiograms: Stratification of "new UK variant" Infection and prediction of in-hospital outcomes. (4th June 2021) - Kotanidis, Christos P; Xie, Cheng; Adlam, David; Rodrigues, Jonathan CL; Siddique, Muhammad; Lockstone, Helen; Thomas, Sheena; Kotronias, Rafail; Oikonomou, Evangelos K; Lumley, Sheila F; Neubauer, Stefan; Newby, David E; et al.
Abstract : Background: Evidence suggests that adverse outcomes in COVID-19 may be driven by a cytokine-induced vascular inflammatory response, caused by SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2). Aim: We aimed to develop a non-invasive method for quantifying cytokine-driven vascular inflammation in patients with acute COVID-19 infection that could allow risk stratification. Methods: We developed a platform for rapid development of novel imaging biomarkers of vascular inflammation, by applying quantitative radiotranscriptomics to images from standard Computed Tomography Angiography (CTA). We used this platform to train a radiotranscriptomic signature (C19-RS) from the perivascular space around the aorta and the internal mammary artery, visualized in routine chest CTAs, to best describe cytokine-driven vascular inflammation, defined using transcriptomic profiles from RNA sequencing data from human arterial biopsies. This signature was tested externally in 435 clinically indicated CT pulmonary angiograms (CTPAs) from patients with or without COVID-19 from 3 different geographical regions. Results: COVID-19 patients were characterised by significantly higher C19-RS values (adjusted odds ratio of 2.97 [95%CI: 1.43–6.27], p=0.004), while patients infected with the new B.1.1.7 variant ("UK variant") were also found to have higher C19-RS values compared to those with the original variant, evidence suggestive of higher degrees of vascular inflammation. C19-RS had prognostic value for in-hospital mortality in COVID-19, with hazard ratios of 3.31 ([95%CI: 1.49–7.33], p=0.003) and 2.58 ([95%CI: 1.10–6.05], p=0.028) in two external testing cohorts respectively, after correction for clinical factors and biochemical biomarkers of inflammation (WBC, CRP) and myocardial injury (troponin). Importantly, the corrected HR for in-hospital mortality was 8.24[95%CI: 2.16–31.36], P=0.002 for those who received no treatment with dexamethasone, but only 2.27[95%CI: 0.69–7.55], p=0.18 in those who received dexamethasone after the test, suggesting that anti-inflammatory treatment may be modifying the natural history of COVID-19 infection by improving outcomes specifically in those patients with high vascular inflammation. Conclusions: Our study introduces a new radiotranscriptomic signature, C19-RS, extracted from routine CTPAs, trained to detect cytokine-driven arterial inflammation, and demonstrates that vascular inflammation determined in this way has prognostic value in patients with COVID-19. The "UK variant" leads to higher vascular inflammation measured in this way, and the risk associated with COVID-19 arteritis is modifiable by dexamethasone.